Comparative Analysis of CDPK Family in Maize, Arabidopsis, Rice, and Sorghum Revealed Potential Targets for Drought Tolerance Improvement - Mittal, Shikha; Mallikarjuna, Mallana Gowdra; Rao, Atmakuri R.; Jain, Prashant A.; Dash, Prasanta K.; Thirunavukkarasu, Nepolean (Frontiers in Chemistry, 2017)
Calcium dependent protein kinases (CDPKs) play major role in regulation of plant growth and development in response to various stresses including drought. A set of 32 CDPK genes identified in maize were further used for searching of orthologs in the model plant Arabidopsis (72) and major food crops such as rice (78) and sorghum (91). We comprehensively investigated the phylogenetic relationship, annotations, gene duplications, gene structure, divergence time, 3-D protein structures and tissue-specific drought induced expression of CDPK genes in all four species. Variation in intron frequency among these species likely contributed to the functional diversity of CDPK genes to various stress responses. Protein kinase and protein kinase C phosphorylation site domains were the most conserved motifs identified in all species. Four groups were identified from the sequence-based phylogenetic analysis, in which maize CDPKs were clustered in group III. The time of divergence (Ka/Ks) analysis revealed that the CDPKs were evolved through stabilizing selection. Expression data showed that the CDPK genes were highly expressed in leaf of maize, rice, and sorghum whereas in Arabidopsis the maximum expression was observed in root. 3-D protein structure were predicted for the nine genes (Arabidopsis: 2, maize: 2, rice: 3 and sorghum: 2) showing differential expression in at least three species. The predicted 3-D structures were further evaluated and validated by Ramachandran plot, ANOLEA, ProSA and Verify-3D. The superimposed 3-D structure of drought-related orthologous proteins retained similar folding pattern owing to their conserved nature. Functional annotation revealed the involvement of CDPK genes in various pathways such as osmotic homeostasis, cell protection and root growth. The interactions of CDPK genes in various pathways play crucial role in imparting drought tolerance through different ABA and MAPK signalling cascades. Our studies suggest that these selected candidate genes could be targeted in development of drought tolerant cultivars in maize, rice and sorghum through appropriate breeding approaches. Our comparative experiments of CDPK genes could also be extended in the drought stress breeding programmes of the related species.